2021
DOI: 10.3390/ijms22115828
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C in Heart Diseases—The Role of Inflammation

Abstract: Tenascin-C (TNC) is a large extracellular matrix (ECM) glycoprotein and an original member of the matricellular protein family. TNC is transiently expressed in the heart during embryonic development, but is rarely detected in normal adults; however, its expression is strongly up-regulated with inflammation. Although neither TNC-knockout nor -overexpressing mice show a distinct phenotype, disease models using genetically engineered mice combined with in vitro experiments have revealed multiple significant roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 191 publications
(279 reference statements)
1
29
0
3
Order By: Relevance
“…The previous study reported the proteome expression in heart failure patients associated with the inflammation response and oxidative stress ( 19 , 22 ), similar to our present study. The inflammation network response to mitral degeneration included the presentation of mitogen-activated protein 3 kinases (MAP3K), kallikrein related peptide (KLK), and tenascin C (TNC).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The previous study reported the proteome expression in heart failure patients associated with the inflammation response and oxidative stress ( 19 , 22 ), similar to our present study. The inflammation network response to mitral degeneration included the presentation of mitogen-activated protein 3 kinases (MAP3K), kallikrein related peptide (KLK), and tenascin C (TNC).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies reported that the use of protein infusions such as kallikrein could improve cardiac function and reduce cardiomyocyte apoptosis and reduce inflammatory cell accumulation in the heart after myocardial ischemia ( 20 , 21 ). Tenascin-C (TN-C) was also another peptide found in the serum of heart failure patients and suggested using it to predict ventricular remodeling and poor prognosis ( 22 ). The proteomic network assessment might be allowed in the evaluation of therapeutic targets for valvular heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In the progression of reactive fibrosis, ‘low-grade (smoldering) chronic inflammation’, mediated by macrophages around the perivascular spaces, might be involved [ 12 , 13 , 14 ]. These patterns usually coexist in most HF patients [ 15 , 16 ], thus it is practically difficult to distinguish between reactive and replacement fibrosis caused by small infarct lesions with low-flow ischemia in the advanced stages of myocardial diseases [ 6 , 7 ].…”
Section: Histological Features Of Cardiac Fibrosismentioning
confidence: 99%
“…αSMA is the most commonly used marker for activated fibroblasts. Tenascin-C (TN-C) is highly expressed in activated CFs and is a potential marker for confirming their phenotype [ 6 , 7 ]. Although these are still under investigation, recent single-cell analyses have revealed several candidate markers that are expressed in cardiac valve interstitial fibroblasts, including wif1 and the cartilage oligomeric matrix protein (COMP) [ 70 ].…”
Section: Cf Markersmentioning
confidence: 99%
See 1 more Smart Citation